Proton conductivity and morphology of new composite membranes based on zirconium phosphates, phosphotungstic acid, and silicic acid for direct hydrocarbon fuel cells applications - Al-Othman, Amani (2016)
The effect of Phosphotungstic acid (PWA) on the proton conductivity and morphology of zirconium phosphate (ZrP), porous polytetrafluoethylene (PTFE), glycerol (GLY) composite membrane was investigated in this work. The composite membranes were synthesized using two approaches: 1) Phosphotungstic acid (PWA) added to phosphoric acid and, 2) PWA + silicic acid were added to phosphoric acid. ZrP was formed inside the pores of PTFE via the in situ precipitation. The membranes were evaluated for their morphology and proton conductivity. The proton conductivity of PWA-ZrP/PTFE/GLY membrane was 0.003 S cm-1. When PWA was combined with silicic acid, the proton conductivity increased from 0.003 to 0.059 S cm-1 (became about 60% of Nafion’s). This conductivity is higher than the proton conductivity of Nafion-silica-PWA membranes reported in the literature. The SEM results showed a porous structure for the modified membranes. The porous structure combined with this reasonable proton conductivity would make these membranes suitable as the electrolyte component in the catalyst layer for direct hydrocarbon fuel cell applications.